AFFECTIVE POSITIONING IN MACEDONIAN INTERNET FORUM DISCUSSIONS (Journal of Contemporary Philology, 2021)
The broader interest of this study is Macedonian internet discourse, particularly how people on the Internet adopt stance towards what they state and towards their interlocutors. The focus here is on affective stance, or the emotional reactions of participants, in two internet forum discussions on the COVID-19 pandemic. Interactional sequences related to alternative explanations, so called conspiracy theories (CTs), have been extracted and manually annotated employing a descriptive framework of evaluative language based on the tenets of systemic functional linguistics. We distinguish four main semantic categories of affect, considering three factors: polarity, orientation and expression. Our interest is mainly in the similarities and differences of affective positioning as expressed by three groups of participants, based on their orientation towards the CTs discussed: supporters, opponents and uncertain. The results show that negative affect prevails, usually as a combination of Insecurity, Unhappiness and Dissatisfaction, triggered by external factors and entities, and most often expressed with a verbal phrase. Expressions of affect appear to serve not only to voice feelings but also to aid stancetaking more generally.
Keywords: Internet discourse; stancetaking; affect; COVID-19